2020
DOI: 10.2147/idr.s242187
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiology and Mortality-Associated Factors of Invasive Fungal Disease in Elderly Patients: A 20-Year Retrospective Study from Southern China</p>

Abstract: Introduction: Invasive fungal disease (IFD) is a life-threatening infection. The epidemiology and clinical features of IFD in the elderly population are less discussed. The aim of this study was to explore the epidemiology and mortality-associated factors for IFD in the elderly inpatients. Methods: A retrospective study enrolling 512 elderly inpatients from The First Affiliated Hospital of Sun Yat-sen University during the last two decades was performed. Results: The annual prevalence of IFD was 0.1-0.5%. Cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In our previous study, we demonstrated that aspergillosis accounts for a growing proportion of invasive fungal diseases in the elderly population during the last two decades. 8 However, much is left to know due to the constraints of space. In the current study, we reported the clinical features of IPA in the elderly population, focusing on co-infections, aiming to provide an in-depth investigation of IPA in the specific population.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that aspergillosis accounts for a growing proportion of invasive fungal diseases in the elderly population during the last two decades. 8 However, much is left to know due to the constraints of space. In the current study, we reported the clinical features of IPA in the elderly population, focusing on co-infections, aiming to provide an in-depth investigation of IPA in the specific population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to an increase in the incidence of IMIs globally and in China, 1–3 , 8 , 31 a gradual increase in patients with COVID-19 co-infected with IA or mucormycosis has also been reported. 32–36 The incidence of invasive pulmonary aspergillosis in patients with COVID-19 ranged from 19.4–33.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that elderly patients may be prone to invasive Candidiasis. It is previously reported that Candida is the most common type of fungus infection in elderly patients [12], with an incidence rate of 45.3%, which may be related to reduced immune function in the elderly [13]. In addition, 28 patients in the disease group gave details of their ward types, showing that patients were mainly concentrated in the emergency intensive care unit and the respiratory and critical care unit (75.00%, 21/28), which was consistent with the report [14].…”
Section: Discussionmentioning
confidence: 99%